Effect of Friction on Electrochemical Reactions from a Thermodynamic Perspective - Chenxu Liu; Yonggang Meng (Recent Developments in Chemistry and Biochemistry Research Vol. 4, 2024)
The effect of friction on the charged solid-liquid interfaces has received more and more attention, especially in the fields of batteries, electrocatalysts and electric vehicles. It is generally considered that friction can interact with electrochemical reactions, causing a rapid failure of materials. In most cases, such as corrosion wear or stress corrosion, the presence of friction or external forces can accelerate electrochemical reactions. Meanwhile, the electrochemical reactions can also increase the wear rate. In other cases, an appropriate friction can inhibit the reaction processes, or even assist the electrochemical processes in achieving unique localized functions of material surfaces. However, the mechanism of the phenomena under electro-mechanical coupling effects has not been revealed yet. In this chapter, the effects of friction force on electrochemical processes are discussed from a thermodynamic perspective. Then, a tribo-electrochemical potential window is introduced by combining the traditional electrochemical potential window with friction/wear maps. The tribo-electrochemical oxides on the wear track of metal surface are characterized, which provides intuitive evidence for the effect of friction on electrochemical reactions. The results provide a better understanding of the solid-liquid interface processes under the electro-mechanical coupling effects in various fields, such as electrocatalysts and electric vehicles.